Persfektif Hukum Perdata Islam mengenai Tradisi Poligami Pada Masyarakat Pauh Kabupaten Musi Rawas Utara - Chaniago, Febry Eraz (Berasan: Journal of Islamic Civil Law, 2023)
The purpose of this study was to find facts about how the tradition of polygamy in the Pauh village community of North Musi Rawas district. This research uses a qualitative approach. The main subjects in this study are all related elements such as village heads or local governments, religious elements, traditional leaders, and polygamous couples themselves. The results showed that the polygamy tradition in Pauh Village, North Musi Rawas Regency has been going on for a long time and there is not half the community that is polygamous. The polygamy incident that occurred in Pauh village is no longer a steadfast thing and has even become a habit among the people of Pauh village. The factor that causes the polygamy tradition carried out by the people of Pauh Village, North Musi Rawas Regency is first, women in the village are willing to be used as honey and do not mind remarrying. Second, economic problems. Third, the habit of having fun with girls. There is a tradition for polygamous women who consider that being a second wife is sufficient or that it is better for her husband to remarry than die. From the side of the villagers, they consider that husbands who only have one wife are less manly so that in the association it becomes a mockery of the community.